PENINGKATAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN CARA ADVERSITY QUOTIENT (AQ) DAN SERVANT LEADERSHIP PADA GURU SMK BERSTATUS PNS SE-KOTA BOGOR - Sri Betty Helena Simamora; Muhamad Entang; Yuyun Elizabeth Patras (JURNAL MANAJEMEN PENDIDIKAN, 2021)
THE IMPROVEMENT OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) BY MEANS OF ADVERSITY QUOTIENT (AQ) AND SERVANT LEADERSHIP OF VOCATIONAL SCHOOL TEACHERS WITH PNS STATUS IN KOTA BOGORThe aim of this research was to explain the increase of Organizational Citizenship Behavior (OCB) by means of Adversity Quotient (AQ) and Servant Leadership. The research was an empirical study using a correlational approach and SITOREM analysis. The research was conducted in several vocational school Bogor by taking teachers with civil servants PNS status. The population in this study was 257 with a sample of 157 respondents that determined by using  Proportional Random Sampling technique. The Hypothesis was tested by using parametric statistical analysis in the form of simple linear regression and multiple analysis, simple and multiple correlation analysis as well as partial correlation analysis where the significance levels a = 0.01 and a = 0.05. The research came up with three conclusions.  Firstly, there was a significant positive relationship between Adversity Quotient and Organizational Citizenship Behavior where its correlation coefficient ry1 = 0.636 and the coefficient of determination ry12 = 0.7172. Secondly, there was a significant positive relationship between Servant Leadership and Organizational Citizenship Behavior where its correlation coefficient ry2= 0.069 and coefficient of determination ry22 = 0.0257. Thirdly, there was a significant positive relationship between Adversity Quotient and Servant Leadership with Organizational Citizenship Behavior where its correlation coefficient ry.12 = 0.4137 and the coefficient of determination ry.122 = 0.7218. It means, in order to improve the Organizational Citizenship Behavior, teachers have to strengthening their Adversity Quotient, and schools’ principal need to have a better Servant Leadership either in group or individually.